(untitled) (Research, Society and Development, 2022)
Aim: to review the literature regarding the scientific production of validation studies of educational technologies for people with respiratory diseases. Methods: integrative literature review carried out in PubMed and VHL databases, using the descriptors: validation study, educational technology, chronic disease, respiratory diseases and their respective ones in English. Studies published in the last 10 years, in all languages, that addressed validation of printed technologies aimed at chronic and acute respiratory diseases were included. Results: Seven articles that met the inclusion criteria in the review were analyzed. Among them, 57.14% (n=4) of the articles were produced in the year 2021, 57.14% (n=4) addressing the validation of educational booklets and 42.85% (n=3) of the productions had the COVID-19 as the subject of educational material. Conclusion: Despite the increase in technology validation, there is a gap in the literature when it comes to respiratory diseases.